Perlindungan Data Pribadi sebagai Pilar Keberlanjutan dan Pertumbuhan Ekonomi Digital di Indonesia - Unggul Sagena; Tukina; Tia Ramda Sari (Journal of Economics, Management, and Accounting, 2025)
Indonesia's rapid digital economic development has positioned personal data as a strategic asset in supporting innovation, efficiency, and public trust in digital services. This study aims to analyze the effectiveness of personal data protection implementation in supporting the stability and growth of Indonesia's digital economy. The method used is a descriptive qualitative approach through secondary data analysis from official government reports, academic publications, and international research institutions. The results show that although regulations have created a comprehensive legal framework, their effectiveness is still hampered by delays in establishing an independent supervisory agency, limited human and technical resources, and low public and business awareness of personal data protection. The economic impact of weak implementation is reflected in declining public trust, increased investment risk, and reduced national digital competitiveness. The success of personal data protection must be seen as a key prerequisite for the sustainability of Indonesia's digital economy through collaboration between the government, the private sector, and the public in creating a secure, transparent, and competitive digital ecosystem.